Cost impact of hydroxocobalamin in the treatment of patients with known or suspected cyanide poisoning due to smoke inhalation from closed-space fires. Issue 6 (September 2022) - Sanders, Kafi N.; Aggarwal, Jyoti; Stephens, Jennifer M.; Michalopoulos, Steven N.; Dalton, Donna; Lewis, Drew E.; Kahn, Steven A.
Highlights: One of the few exploratory studies to determine the economic implications of hydroxocobalamin. A decision analysis model was developed from the US hospital perspective using a retrospective evaluation of clinical outcomes (Nguyen, et al. 2017). Use of hydroxocobalamin contributes to decreased per-patient hospital costs (15, 381 with hydroxocobalamin versus 22, 607 with no antidote). The most substantive cost-savings resulted from decreased hospital length of stay. Use of hydroxocobalamin may decrease hospital costs and contribute to more efficient healthcare resource utilization. Abstract: Background & objectives: Cyanide poisoning can occur due to exposure to smoke in closed-space fires. With no point of care cyanide test at the scene of a fire, first responders and clinicians base decisions to treat with cyanide antidote on patient history, clinical signs, and other indirect data points that have not been proven to correspond with actual systemic levels of cyanide. The aim of this exploratory study was to determine the economic implications of treating patients with known or suspected cyanide poisoning due to smoke inhalation with hydroxocobalamin. Methods: A decision analysis model was developed from the US hospital perspective. Healthcare resource utilization was estimated from a retrospective evaluation of clinical outcomes in hydroxocobalamin-treated patients and in historical controls without hydroxocobalamin use (Nguyen, et al. 2017). Epidemiologic parameters and costs were estimated from the published literature, and publicly-available hospital charges were identified. Outcomes reported in the analysis included expected healthcare resource utilization in the US population and per-patient costs with and without the use of hydroxocobalamin. A cost-to-charge ratio was applied so that all costs would reflect hospital costs rather than hospital charges. Deterministic sensitivity analysis was performed to identify the most influential model parameters. All costs were reported in 2017 US dollars. Results: Use of hydroxocobalamin reduces healthcare resource utilization and contributes to decreased per-patient hospital costs (15, 381 with hydroxocobalamin treatment versus 22, 607 with no cyanide antidote). The most substantive cost-savings resulted from decreased hospital length of stay (i.e., intensive care unit [ICU] and non-ICU). Costs attributed to mechanical ventilation also decreased with use of hydroxocobalamin. A univariate sensitivity analysis demonstrated that the most impactful variables in the cost analysis were related to hospital length of stay (ICU followed by non-ICU stay), followed by the daily cost of ICU stay. Conclusions: Use of hydroxocobalamin in patients with known or suspected cyanide poisoning from closed-space fire smoke inhalation may decrease hospital costs and contribute to more efficient healthcare resource utilization.